Indicative nutrient supplying capacity and chemical properties of coir dust, coco husk and other coir dust-based materials - Ma. Celia M. Raquepo; Carmelita D. Pabustan; Severino S. Magat (International Coconut Community, 2004)
The variability of the nutrient contents and chemical properties of coir dust or coco peat derived from coconut husk in different locations was noted. Coir dust is a good supplementary source of N, P, K and Cl, including micronutrients (B, Cu, Fe, Zn, Mn). The coir dust acidity ranges from pH 5.2 - 7.0, and EC from 0.10-1.67 ms/cm based from: fresh (1 month), 3 – 5 months, and 1 year open-field piling (storage). Higher contents of nutrients K, Cl, and Fe of coir dust under coastal area was noted; but contents of N, P, Ca, Mg, S, B, Zn, Mn and Cu were found similar in coastal and inland areas. Under rainfall in open-field piling, Cl dropped to <0.25% at 3 – 5 months and <0.12% in a year’s time period. Moreover, a significant reduction of <0.30 and <0.15 EC (m/cm) in mentioned periods were indicated, respectively. Generally, as compared with other nut components, coco husk and the coir dust did not differ in nutrient contents and chemical properties. As composting material, either alone or in mixes, coco peat showed to be a supplementary source of P, K and Cl. NPK ratio was 2:1:2; and organic carbon content ranged from 6.34 - 12.07%